2004
DOI: 10.1177/004051750407400709
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Performance of Elastic Core-Spun Yarn

Abstract: In this experiment, we use a 44.4 dtex/4f spandex filament as the core and cotton fibers as the sheath to spin 19.7 tex elastic core-spun yarn. In order to improve yarn performance, we examine the yams cross-sectional structure and investigate the effect of draw ratio and feed-in angle of the spandex on the yarns' structure and performance. The results show that a higher feed-in angle provides a better cover effect and a draw ratio of 3.5 yields better dynamic elastic recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 7 publications
2
57
0
1
Order By: Relevance
“…This problem could be reduced to a large extent by improved control of the relative movement between the roving and the filament, e.g. by using commercial core-yarn spinning attachments (Bbaarslan & Celik, 2001;Kakvan et al, 2007;König, 2002;Su et al, 2004). The most common commercial design of a filament positioning device is a grooved roller frictionally driven on the top front drafting roller.…”
Section: Conventional Roving Feedingmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem could be reduced to a large extent by improved control of the relative movement between the roving and the filament, e.g. by using commercial core-yarn spinning attachments (Bbaarslan & Celik, 2001;Kakvan et al, 2007;König, 2002;Su et al, 2004). The most common commercial design of a filament positioning device is a grooved roller frictionally driven on the top front drafting roller.…”
Section: Conventional Roving Feedingmentioning
confidence: 99%
“…The results were expressed in percentage of uncovered area on the yarn. Su, Maa, and Yang (2004) studied elastane core-yarn coverage by sectioning the yarn and examining the radial position of the core. The most important spinning conditions influencing the yarn coverage and resistance to strip-back are the filament feeding tension and the filament/roving feeding configuration in the yarn formation zone (Balasubramanian * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In core spun yarns, there is an elastomeric filament in the core and around it staple fibers are wrapped. Consequently, the resultant fabric has all the characteristics of the predominant staple fiber together with the advantages of stretch and recovery (Su, Maa, & Yang, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Babaarslan [9] and Dang et al [10] produced an elastic core spun yarn by using an elastic filament in core. Su et al [11], investigated the structure and the performance of the elastic core spun yarns. They confirmed that the feeding angle and draft ratio influence the filament position depending on the material used.…”
Section: Introductionmentioning
confidence: 99%